Green control for inhibiting Rhizopus oryzae growth by stress factors in forage grass factory - Dai, Mengdi; Tan, Xiangfeng; Chen, Xuting; Cai, Kangfeng; Zhong, Yuanxiang; Ye, Ziran; Kong, Dedong (Frontiers in Microbiology, 2024)
The forage grass factory could break through the restrictions of land resources, region and climate to achieve efficient production throughout the year by accurate and intelligent management. However, due to its closed environment, mold outbreaks in the forage grass factory were severe, significantly affecting barley production. In this study, 9 contaminated barley tissues were collected and 45 strains were isolated in forage grass factory. After ITS sequencing, 45 strains were all identified as Rhizopus oryzae. Through stress factor assays, R. oryzae growth was seriously hindered by low concentration of sodium nitrate, high pH value and ozone water treatment. High pH and ozone water affected growth mainly by altering membrane integrity of R. oryzae. Sodium nitrate inhibited the growth of R. oryzae mainly by affecting the amount of sporulation. Low concentration of sodium nitrate and ozone water did not affect the growth of barley. High concentrations of sodium nitrate (100 mM) and pH values (8-8.5) inhibited barley growth. Among them, ozone water had the most obvious inhibition effect on R. oryzae. Large-scale ozone water treatment in the forage grass factory had also played a role in restoring barley production. Taken together, the green techonology to control mold disease and maintain the safety of forage through different physicochemical methods was selected, which was of considerable application value in animal husbandry.